Waste to Energy Sustainability Model as a Waste Power Plant: A Bibliometric and Visualization Analysis - Rachmawatie, Dessy; Erwin, Erwin; Irawaty, Khafidza Nisa (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
More than half of the world's population lives in cities, so the increase in urban waste production globally is mainly due to population growth, urbanization, and economic development, in the past decade, the utilization of waste to energy has provided positive benefits in terms of energy generation. By 2040 power generation will increase globally by 49%. By 2040, renewable energy sources are expected to meet 8% of the total global energy demand, With the development of the economy, waste management goes through several stages to reach the level of high technology as seen today. A sophisticated collection system, combined with an efficient separation process, enables high recovery and recycling rates. The method used in this study is qualitative with a literature study approach. The findings in this study show that China is the country that researches the most about wasto to energy, then the process carried out in the PLTSa Waste to Energy Policy Model recommendations in this study involves several related actors such as Business Entities, authorized Local Governments, and communities. In this case, waste to energy needs attention by local governments that have the authority to manage electricity by establishing provincial regulations in the electricity sector, establishing general electricity plans, and determining business licenses for providing electricity to business entities.